The Boom in Corporate Borrowing after the Global Financial Crisis : Different Tales from East Asia and Latin America - Abraham, Facundo; Cortina, Juan J.; Schmukler, Sergio L. (World Bank, Washington, DC, 2021)
Firms from emerging economies increased their bond financing significantly after the 2008-09 global financial crisis. The patterns of corporate borrowing in East Asia and Latin America offer very different lessons. In East Asia, the main component behind the overall growth in bond financing was an expansion in domestic bond issuances, in domestic currency, by more and smaller firms. This expansion seems to be explained by a higher supply of funds by domestic investors, which lowered issuance costs. In Latin America, relatively larger firms tended to borrow from international markets issuing foreign currency bonds. These contrasting patterns have resulted in exposures to different types of risks. Risks in East Asia have been more related to the increasing debt accumulation by smaller firms, issuing debt at shorter maturities. Latin American firms have been more exposed to external factors and currency depreciations.